Information sources used by Nigerian lawyers for task-related activities - Adewale, Nafisat; Mansor, Yushiana (DE GRUYTER, 2014)
Studies on information seeking behaviour have shown that workers, especially professionals look for in- formation in order to perform their work related activities. Because the legal profession is an information-intensive one, understanding the sources consulted by lawyers for their task performance is important for librarians as ser- vice providers in order to ensure effective and efficient ser- vice delivery. This study seeks to understand the sources that are consulted by lawyers for specific job-related tasks they perform. Data was gathered using questionnaires from a total of 64 lawyers in Kwara State, Nigeria. Findings show that the sources consulted by lawyers are related to the kind of tasks they perform. While human sources are mostly consulted for the performance of tasks involving interpersonal communications such as negotiations and settling disputes out of court, the advocacy task requires that they consult authorised sources such as legal publi- cations and literatures. However, a generally low use of electronic sources (such as e-databases and e-journals) was observed among lawyers.